Investigations into Potential Extrasynaptic Communication between the Dopaminergic and Nitrergic Systems - Mitkovski, Miso; Padovan-Neto, Fernando E.; Raisman-Vozari, Rita; Ginestet, Laure; Da-Silva, Celia; Del Bel, Elaine (Frontiers in Physiology, 2012)
Nitric oxide is unconstrained by cell membranes and can therefore act along a broad distance as a volume transmitter. Spillover of nitric oxide between neurons may have a major impact on central nervous system diseases and particularly on neurodegeneration. There is evidence whereby communication between nitrergic and dopaminergic systems plays an essential role in the control of the nigrostriatal pathway. However, there is sparse information for either the coexistence or overlap of nitric oxide and dopaminergic structures. The dual localization of immunoreactivity for nitric oxide synthase (NOS) and tyrosine hydroxylase, enzymes responsible for the synthesis of nitric oxide and dopamine, respectively, was examined in neurons of the nigrostriatal pathway in the rat brain by means of a double-immunohistochemical method and confocal laser scanning microscopy, acquired at the resolution limit. After perfusional fixation, the brains were cut and double-immunostained. A proximity analysis of tyrosine hydroxylase and NOS structures was done using binary masks generated from the respective maximum projections, using confocal laser microscopy. Unrevealed regions were determined somatodendritic positive for both NOS and tyrosine hydroxylase, within an image limit resolution at 2 μm-wide margin. The described interconnected localization of nNOS(+) and TH(+) containing neuronal fibers and cells bodies in the nigrostriatal pathway propose a close anatomical link between the two neurotransmitters.